Educação em uma perspectiva humanizadora: percepção de educandos com deficiência intelectual no curso de Pedagogia, das Unidades Universitárias de Goianésia e Jaraguá, na Universidade Estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This dissertation, inserted in Research Line 2: Culture, School, and Formation, of the Graduate Program in Education, at the State University of Goiás, in the University Unit of Inhumas/Goiás (PPGE/UEG/Inhumas), addresses the education of individuals with intellectual disabilities in Higher Education Institutions, focusing on the perspective of humanizing education, based on Paulo Freire. For this purpose, the guiding question was established: how can the perceptions of students with intellectual disabilities in the Pedagogy course at UEG, in the University Units of Goianésia and Jaraguá, contribute to reflections on humanized education processes and educational praxis in Higher Education? The general objective was to unveil, based on the perceptions of students with intellectual disabilities in the Pedagogy course at UEG, in the University Units of Goianésia and Jaraguá, the processes of humanized education in order to contribute to reflections on educational praxis in Higher Education. The research adopts a qualitative and bibliographical approach, grounded in documents. It involved the participation of 03 students with intellectual disabilities enrolled and regularly attending the Pedagogy course at UEG, in the University Units of Goianésia and Jaraguá, as well as the director of the Intersectoral Center for Human Rights, Accessibility, and Actions - NIAAF/UEG. The method adopted the approach of phenomenological methodology (Bicudo, 2011; Moreira, 2004) to give due relevance to the process experienced and perceived by the participants, with Minayo's dialectical hermeneutics (2002; 2014; 2016) providing the guidelines for understanding and interpreting the entire research. It is based on authors dealing with this theme, such as Merleau-Ponty (2018) regarding "perception"; "Special Education" and the perspective of "difference" from the reflections of Skliar (2013), Picollo (2013, 2019; 2022a; 2022b), and Denari (2006; 2015, 2019); "disability" - and as part of this category, the specificity of "intellectual disability" - from the social model, the research relies on the Brazilian Inclusion Law (Brazil, 2015a), Omote (2005; 2018), Harlos (2012, 2015), and the social movement called the Union of The Physically Impaired Against Segregation – UPIAS; the category of "stigma" had its theoretical basis in Goffman (2022), as well as the perspective of Paulo Freire (1980; 1983; 2020) and Arendt (2020) categorize the "human being" and, together with Adorno (2020), propose the conception of education as a humanizing possibility and liberating practice; and Coêlho (2009, 2012a, 2012b; 2016) and Guimarães (2020) to substantiate the category of "education and human formation" with the approach of Freirean foundations; regarding "otherness," the theoretical assumptions of Freire (1980. 1983, 2020) and Reis (2013; 2021) were used, as well as official documents: National Education Guidelines and Bases Law (LDBEN, 1996); Brazilian Inclusion Law (LBI, 2015a). The results indicated that the perceptions of the students contributed to reflections on humanized education processes and educational praxis in Higher Education, opening opportunities to weave knowledge about the academic environment and to consider the possibility that this environment be permeated by a dialogical praxis involving these students, their families, and the entire school community.
Education from a humanizing perspective: perceptions of students with intellectual disabilities in the Pedagogy course, at the University Units of Goianésia and Jaraguá, at the State University of Goiás
Keywords: Educação; Deficiência intelectual; Educação Superior; Humanização; Paulo Freire; Education; Intellectual disability; Higher education.; Humanization; EDUCACAO::ENSINO-APRENDIZAGEM